Upaya peningkatan hasil belajar passing bawah permainan bola voli dengan metode kerja kelompok pada siswa kelas X - Muhammad Thowil Makhis (Persatuan Guru Republik Indonesia Kota Banjarbaru, 2021)
Volleyball game lessons are in demand by most students because of their nature to play and compete. However, the reality on the ground is that there are still many obstacles encountered in the implementation of volleyball game learning. One alternative that can be used to solve these problems is the group work method. The group work method in physical education is a step in presenting lessons by means of students doing assignments in group situations under the guidance of the teacher. The purpose of this study was to determine the learning outcomes of the application of the group work method in students' learning of passing down the volleyball game. This research has a quantitative descriptive approach and is a Class Action Research (CAR). The subjects of this study were 40 students of class X MIPA 2 SMA Negeri Balung, Jember Regency. Data collection techniques with observation. The data analysis technique used in this research is triangulation. The results of the study stated that in cycle 1, students who scored B = 0%, C = 51% and D = 49%. In cycle 2 there is an increase in the value of B = 5%, the value of C = 60% and the value of D = 5%. While in the fourth cycle the value of D: 0%, the value of C = 5%. These results indicate that the application of the group work method is effective in improving student learning outcomes in the subject of passing down the volleyball game for class X SMA Negeri Balung, Jember Regency.